Kendra Keely: capstone - Keely, Kendra, artist (Colorado State University. Libraries, 2016)
The artist's statement: I started my love of graphic design through photography. My photography allowed me to express my ideas and feelings in a way that was unique to me and was essentially a self-expressive media. I first took a graphic design class sophomore year of college and ended up learning a lot about what it means to apply my work in a way that reaches a larger public and has a chance to impact people in a different way. Graphic design is a way to engage an audience and also give them the information they need in real life applications. I want my design to be able to reach people and express an idea in a creative way that shows my vision but is also more oriented toward a purpose. I love the freedom that graphic design provides and the endless mediums that can be utilized in a design. It is all encompassing and the creativity is endless. I strive to obtain this freedom and express my creative vision through my design.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design